The features of modern business culture of Japan - Кaгaзбaевa, Э. М.; Бaктыбековa, Б Б. (Journal of Oriental Studies, 2018)
In the given article were investigated the features of modern business culture of Japan. The uniqueness of Japanese culture is explained through historical peculiarities of development, height density of population, driven by geographical position and specific of Japanese language. Cultural and historical values which influence on business culture of Japan were analyzed. Authors came to conclusion that disability of Japanese people to exchange and adopt elements from other culture, while preserving the national cultural heritage by their own, strengthened in them a sense of of their own exclusivity. Japanese business ethics is inextricably linked with the culture of the country and the ethnopsychology of the Japanese people.